Residents’ perceptions, attitudes and support towards rural tourism - Pato, Lúcia (2017)
This research analyses residents’ perceptions on the effects of rural tourism in two regions of Portugal, namely in Dão-Lafões Region and Douro Region. Although residents do not develop negative environmental and sociocultural perceptions with regards to tourism, they agree that it only benefits a small number of residents, thus widening the gap between the rich and poor in these regions. It is also proposed that there are different patterns of residents´ support depending on their differential benefits obtained from tourism. In fact, the hypotheses between different constructs that affect residents’ perceptions and support were tested with Mann-Whitney and Spearman Rho tests. The results confirmed the existence of significant relationships between personal benefits received and both positive and negative perceptions developed by residents and their satisfaction and support of tourism. It is further considered that the outcomes of the research should be taken into consideration in the process of creation and implementation of strategies aimed towards contributing to a model of tourism development that puts people in the spotlight and can thus contribute to the planning and managing of these regions more appropriately.